Effect of family empowerment model on quality of life in children with chronic kidney diseases - Ghazavi, Zohreh (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Quality of life is a concept, which in recent years is considered as a measure for health in chronic diseases such as kidney diseases. Complications of chronic diseases can affect the quality of life in children and their families over time. Therefore, empowerment programs are necessary to improve their quality of life. This study aimed to investigate the impact of the family empowerment model on the quality of life in children with chronic kidney diseases. MATERIALS AND METHODS: This quasi-experimental study was conducted on 64 children with chronic kidney diseases and their families. The research tools included the questionnaire of demographic characteristics and the quality of life questionnaire 4(th) edition. After data collection in the first phase, the family empowerment model was implemented in the intervention group and the test was repeated after 1 month. For comparison of data between the two groups and within each group, independent t-test and paired t-test were used, respectively. RESULTS: Independent t-test showed that the mean score of quality of life was not significantly different in the two groups before intervention. However, after intervention, the differences were significant. Paired t-test showed a significant difference in the quality of life before and after intervention in the study group. CONCLUSIONS: The findings showed that family empowerment model was effective in increasing the quality of life of children with chronic kidney diseases. Thus, we suggest this model to be used in inpatient and outpatient children's health care.